Long‐term dietary quercetin enrichment as a cardioprotective countermeasure in mdx mice. Issue 6 (30th March 2017) - Ballmann, Christopher; Denney, Thomas; Beyers, Ronald J.; Quindry, Tiffany; Romero, Matthew; Selsby, Joshua T.; Quindry, John C.
Abstract : New Findings: What is the central question of this study? The central question of this study is to understand whether dietary quercetin enrichment attenuates physiologic, histological, and biochemical indices of cardiac pathology. What is the main finding and its importance? Novel findings from this investigation, in comparison to prior published studies, suggest that mouse strain‐dependent cardiac outcomes in performance and remodelling exist. Unlike Mdx / Utrn −/+ mice, mdx mice receiving lifelong quercetin treatment did not exhibit improvements cardiac function. Similar to prior work in Mdx / Utrn −/+ mice, histological evidence of remodelling suggests that quercetin consumption may have benefited hearts of mdx mice. Positive outcomes may be related to indirect markers that suggest improved mitochondrial wellbeing and to selected indices of inflammation that were lower in hearts from quercetin‐fed mice. Duchenne muscular dystrophy causes a decline in cardiac health, resulting in premature mortality. As a potential countermeasure, quercetin is a polyphenol possessing inherent anti‐inflammatory and antioxidant effects that activate proliferator‐activated γ coactivator 1α (PGC‐1α), increasing the abundance of mitochondrial biogenesis proteins. We investigated the extent to which lifelong 0.2% dietary quercetin enrichment attenuates dystrophic cardiopathology in mdx mice. Dystrophic animals were fed a quercetin‐enriched or control diet for 12 months, while control C57 mice were fed a control diet. Cardiac function was assessed via 7 T magnetic resonance imaging at 2, 10 and 14 months. At 14 months, hearts were harvested for histology and Western blotting. The results indicated an mdx strain‐dependent decline in cardiac performance at 14 months and that dietary quercetin enrichment did not attenuate functional losses. In contrast, histological analyses provided evidence that quercetin feeding was associated with decreased fibronectin and indirect damage indices (Haematoxylin and Eosin) compared with untreated mdx mice. Dietary quercetin enrichment increased cardiac protein abundance of PGC‐1α, cytochrome  c, electron transport chain complexes I–V, citrate synthase, superoxide dismutase 2 and glutathione peroxidase (GPX) versus untreated mdx mice. The protein abundance of the inflammatory markers nuclear factor‐κB, phosphorylated nuclear factor kappa beta (P‐NFκB) and phosphorylated nuclear factor of kappa light polypeptide gene enhancer in B‐cells inhibitor alpha (P‐IKBα) was decreased by quercetin compared with untreated mdx mice, while preserving nuclear factor of kappa light polypeptide gene enhancer in B‐cells inhibitor alpha( IKBα) compared with mdx mice. Furthermore, quercetin decreased transforming growth factor‐β1, cyclooxygenase‐2 (COX2) and macrophage‐restricted F4/80 protein (F4/80) versus untreated mdx mice. The data suggest that long‐term quercetin enrichment does not impact physiological parameters of cardiac function but improves indices of mitochondrial biogenesis and antioxidant enzymes, facilitates dystrophin‐associated glycoprotein complex (DGC) assembly and decreases inflammation in dystrophic hearts. Abstract :